Dampak Adopsi FinTech dalam Meningkatkan Inklusi Keuangan di Indonesia: Pendekatan Systematic Literature Review - Wulandari Agustiningsih (Jurnal Riset Mahasiswa Akuntansi, 2026)
This study aims to map the relationship between FinTech and financial inclusion in Indonesia, focusing on urban-rural comparisons and the role of financial literacy. Using a Systematic Literature Review (SLR) approach, this study screened and analyzed 20 accredited scientific articles from the Scopus, Web of Science, and Google Scholar databases published in the last ten years. The review results indicate that FinTech P2P lending and digital payments contribute positively to financial inclusion and poverty reduction, with the important finding that Islamic financial inclusion through FinTech is positively correlated with the Human Development Index. However, there are significant differences between urban and rural areas in terms of the influence of digital financial literacy on adoption intentions and government support for usage behavior. This study concludes that the effectiveness of FinTech in driving financial inclusion is highly dependent on geographic context and literacy levels, thus requiring different policy approaches between urban and rural areas, as well as strengthening digital financial literacy as a prerequisite for sustainable inclusion.